Utility of scatterplot patterns of automated hematology analysers in white blood cell disorders – A comparative study with peripheral blood smears - Gupta, Tavish; Basu, Debdatta (Asian Journal of Medical Sciences, 2020)
Background: Advances in automated blood cell counting offer new possibilities to analyse leukocyte differentials by fluorescence RNA/DNA staining combined with scattered light intensity technologies. Aims and Objectives: The purpose of this study is to identify the scatterplot patterns in normal cell counts and various White Blood Cell (WBC) disorders and to assess their efficacy compared to a peripheral blood smear (PBS) in the diagnosis of WBC disorders. Materials and Methods: A three-phased descriptive study analysing a total of 933 EDTA blood samples. The total leucocyte count, differential leucocyte count, scatterplot patterns as obtained by automated cell counter and PBS were studied in 405 normal samples (Phase 1) and 415 samples with WBC abnormalities (Phase 2). In phase 3, the scatterplots of 113 abnormal flagged samples were analysed and provisional diagnosis made in each case which was then compared with the diagnosis on the PBS. Sensitivity, Specificity, Positive and Negative predictive values (PPV & NPV) were calculated. Results: A grid-based standard scatterplot of normal samples was generated as a reference plot in phase one. Based on the scatterplots obtained in known WBC abnormalities studied in phase two, the basic abnormal patterns specific to each of the individual abnormalities were discerned. The phase three study showed excellent correlation between scatterplots and PBS findings in neutrophilia, eosinophilia, lymphocytosis and leukopenia (sensitivity 92-100%, specificity 98-100%). Abnormalities suspected to be leukemia on the scatterplots had a relatively low sensitivity and PPV. Conclusion: WBC scatterplots can be used as a screening tool as it correlates well with various WBC disorders in the PBS.